2022
DOI: 10.3390/toxins14070457
|View full text |Cite
|
Sign up to set email alerts
|

In-House Validation of an Efficient and Rapid Procedure for the Simultaneous Determination and Monitoring of 23 Mycotoxins in Grains in Korea

Abstract: A high-performance liquid chromatography tandem mass spectrometry method is described for the simultaneous determination of mycotoxins, including Ergot alkaloids (EAs), in 3 types of grains. The extraction of 23 mycotoxins was evaluated and performed by using a modified QuEChERS-based sample preparation procedure. The proposed method was fully validated on spiked grain samples (barley, wheat and oat) to assess the linearity, limit of detection (LOD) and limit of quantitation (LOQ), matrix effects, precision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results, as shown in Table 4, showed that the LOQs of the present method for pesticide residues were significantly lower than those of ref. 41–43. Meanwhile, for the detection of mycotoxins, the LOQs of the present method were all less than or equal to those of ref.…”
Section: Resultsmentioning
confidence: 58%
“…The results, as shown in Table 4, showed that the LOQs of the present method for pesticide residues were significantly lower than those of ref. 41–43. Meanwhile, for the detection of mycotoxins, the LOQs of the present method were all less than or equal to those of ref.…”
Section: Resultsmentioning
confidence: 58%
“…As well as extracting the analytes of choice from the matrix, one of the main issues is the co-extraction of matrix compounds and the associated matrix effects, which can lead to issues with the analysis. These include, but are not limited to: signal suppression or enhancement (SSE), poor chromatography, false positives due to the presence of isobaric compounds and poor or incomplete recovery of the target analytes [ 126 ]. Therefore, after the initial extraction, a sample clean-up step is usually employed in order to remove as much matrix as possible before analysis, which also serves to decrease the limit of detection (LOD) and limit of quantification (LOQ) should this be a requirement.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining water and other interfering substances from the matrix are eliminated in this stage [ 65 ]. There are several methods using the QuEChERS protocols for the extraction and clean-up of mycotoxins before instrumental analysis [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Sampling and Sample Preparation Methodsmentioning
confidence: 99%